Regional initiatives on nuclear- and WMD-free zones : cooperative approaches to arms control and non-proliferation - Hamel-Green, Michael (UNIDIR, 2005)
The initial years of the new millennium have seen little substantive progress in nuclear arms control and indeed many setbacks. Despite these discouraging developments, however, there is still considerable need, and potential, for progress to be made in nuclear arms control at a regional level, namely through of the consolidation and expansion of nuclear-weapon-free zones (NWFZs). The present study discusses the status and benefits of existing and proposed NWFZs.--Publisher's description.